Analysis of differential expression of matrix metalloproteinases and defensins in the nasopharyngeal milieu of mild and severe COVID-19 cases - Khekashan Imtiaz; Nida Farooqui; Khalid Ahmed; Alnara Zhamalbekova; Muhammad Faraz Anwar; Asghar Nasir; Zeeshan Ansar; Khitab Gul; Azhar Hussain; Antonio Sarría-Santamera; Syed Hani Abidi (PLoS ONE, 2025)
Introduction A subset of COVID-19 disease patients suffers a severe form of the illness; however, underlying early pathophysiological mechanisms associated with the severe form of COVID-19 disease remain to be fully understood. Several studies showed the association of COVID-19 disease severity with the changes in the expression profile of various matrix metalloproteinases (MMPs) and defensins (DA). However, the link between the changes in the expression of MMPs and DA in the nasopharyngeal milieu during early phases of infection and disease severity remains poorly understood. Therefore, we performed differential gene expression analysis of MMPs and DA in the nasopharyngeal swab samples collected from normal (COVID-19 negative), mild, and severe COVID-19 cases and examined the association between MMP and DA expression and disease severity. Material and method A total of 118 previously collected nasopharyngeal samples from mild and severe COVID-19 patients (as per the WHO criteria) and 10 healthy individuals (COVID-19 negative, controls) were used in this study. A real-time qPCR assay was used to determine the viral loads and assess the mRNA expression of MMPs and DA. One-way ANOVA was applied to perform multiple comparisons (estimate differences) in MMPs and defensin gene expression in the normal vs mild vs severe groups. In addition, a multivariable logistic regression analysis was carried out with all the variables from the data set using ‘severity’ as the outcome variable. Results Our results showed that as compared to controls, DA1, DA3, and DA4 expression was significantly (p < 0.05) upregulated in the mild group, whereas the expression of DA6 was significantly downregulated in both mild and severe groups (p-value < 0.05). Similarly, compared to controls, the expression of MMP1 and MMP7 was significantly downregulated in both mild and severe groups, whereas MMP2 expression was upregulated in the mild group (p-value < 0.05). Additionally, the regression analysis showed that the expression of MMP1, MMP2, and MMP9 was significantly associated with the severity of the disease. Conclusion The early detection of changes in the expression of MMPs and defensins may act as a useful biomarker/predictor for possible severe COVID-19 disease, which may be useful in the clinical management of patients to reduce COVID-19-associated morbidity and mortality.